2018
DOI: 10.1002/jwmg.21441
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and predator interactions affect northern bobwhite behavior

Abstract: Anti‐predator behavior can be costly to prey species and the consequences of these decisions may affect survival. Interactions between humans and hunted species can lead to behavioral shifts in the animal that affect hunter satisfaction and possibly fitness of the animals. We assessed the influence of multiple factors that may affect anti‐predator behavior in a commonly harvested game bird, the northern bobwhite (Colinus virginianus), during October 2013–March 2015 on a private plantation in South Carolina, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Our results contribute to the growing body of literature demonstrating that game species perceive hunters as predators and shift resource selection to avoid predation risk (Ordiz et al 2012, Gross et al 2015, McGrath et al 2018, Wightman et al 2023a). We specifically investigated how male resource selection changed prior to and within the hunting season in response to hunter distribution.…”
Section: Discussionsupporting
confidence: 66%
“…Our results contribute to the growing body of literature demonstrating that game species perceive hunters as predators and shift resource selection to avoid predation risk (Ordiz et al 2012, Gross et al 2015, McGrath et al 2018, Wightman et al 2023a). We specifically investigated how male resource selection changed prior to and within the hunting season in response to hunter distribution.…”
Section: Discussionsupporting
confidence: 66%
“…It is plausible that increased movement prior to contact with a hunter resulted from males responding to a call and traveling toward the call at a speed faster than average. Conversely, we offer that increased movements after a contact with a hunter were likely due to a fleeing response by males after they became aware of the hunter's presence (Courbin et al, 2015; Gross et al, 2015; McGrath et al, 2018; Middleton et al, 2013). Given that increased movements may result in demographic effects (Suraci et al, 2022), future studies should investigate potential relationships between variation in movement behaviors and survival of male turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that at the third-order of selection, bobwhite would optimize trade-offs between concealment and unobstructed flight paths to escape predators. Previous research on coveys indicates that bobwhite make context-specific evasive maneuvers when disturbed by predators (McGrath et al 2018). McGrath et al (2018 also demonstrated that visual obstruction of vegetation influenced the type of evasive maneuvers used.…”
Section: Introductionmentioning
confidence: 97%